How We Invest. Issue 2 (20th July 2017) - Bloomberg, Michael; Pope, Carl
Abstract : In this chapter from their new book, Climate of Hope: How Cities, Businesses, and Citizens Can Save the Planet, the founder of Bloomberg LP and former mayor of New York City collaborates with the former executive director of the Sierra Club in showing how the pursuit of profit by companies and their investors is playing an important role in the battle against global warming. Climate change is shown as posing a series of discrete, manageable challenges—such as accelerating the transition from fossil fuels to clean energy—that have spurred a search for solutions that promise to make our society healthier and stronger. National governments, the authors argue, are not the best places to create or carry out these solutions. Rather, it is the mayors, CEOs, entrepreneurs, activists, concerned citizens, and other local actors who have the strongest incentives as well as the power and means to win the battle against climate change—and in ways that have already begun to generate economic growth and improve public health. State governors and mayors of cities around the U.S., in red and blue states alike, have been responsible for much of this progress. Cities and states have negotiated contracts with local utilities to provide greater amounts of clean energy, and used combinations of public and private capital to fund rapid transit, waste‐water treatment, and other infrastructure programs. But an equally important if not larger role is now being played by business. Companies large and small, with the backing of a growing number of environmentally conscious but resolutely profit‐seeking investors, are finding ways to reduce waste and strengthen worker protection and morale throughout supply chains that are providing increasingly climatefriendly products and services. The authors' bottom line, then, is that preventing climate change will require more than goodwill and government regulation. It will take the profit motive, a force that that many environmentalists have long viewed with suspicion. While acknowledging the past efforts of socially responsible investment funds that have shown a willingness to sacrifice returns, the authors conclude that the enlightened self‐interest of value‐seeking investors may well prove more effective than the "beneficence" of social investors and philanthropists in producing investments of sufficient scale and practical efficacy to meet the challenges of global warming.